Significance of Vivekananda's Practical Vedanta: Today and Tomorrow (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
Swami Vivekananda's philosophy of Practical Vedanta represents a revolutionary synthesis of ancient Indian spiritual wisdom and modern pragmatic application. This research examines the contemporary relevance and future implications of Vivekananda's teachings, which bridge the gap between metaphysical speculation and practical life. Through comprehensive analysis of his works and their impact on various domains including education, social reform, interfaith dialogue, and personal development, this study demonstrates how Practical Vedanta offers viable solutions to current global challenges while providing a framework for future human development. The research employs qualitative methodology, drawing from primary sources, scholarly interpretations, and contemporary applications to establish the enduring significance of Vivekananda's philosophical contributions in addressing modern existential, social, and spiritual concerns.